THE PERSON WITH STROKE IN REHABILITATION PROCESS: GAINS FROM THE INTERVENTION OF REHABILITATION NURSES - Jéssica Santos; Manuela Martins; Célia Campos (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Introduction: Cerebrovascular diseases are one of the main causes of death and morbidity in Portugal, causing disability and invalidity. Objective: To analyze the health gains of a stroke patient after implementing a Rehabilitation Program. Method: Case study of a patient who suffered a stroke, of a descriptive nature, in an inpatient service of a North Coast Hospital in the country, for 30 days. Results: After the implementation of the Rehabilitation Program, there was an improvement in body balance, muscle strength, capacity for self-care and swallowing and decreased risk of falling. Conclusion: The intervention of the Rehabilitation Nurse brings gains in the functional recovery of stroke patients, contributing to their autonomy in activities of daily living.